EBK NONLINEAR DYNAMICS AND CHAOS WITH S
EBK NONLINEAR DYNAMICS AND CHAOS WITH S
2nd Edition
ISBN: 9780429680151
Author: STROGATZ
Publisher: VST
bartleby

Videos

Question
Book Icon
Chapter 7.6, Problem 25E
Interpretation Introduction

Interpretation:

Consider the weakly nonlinear oscillator x¨ + x + εh(x,x˙,t) = 0. Let x(t) = r(t)cos (t+ϕ(t)), x˙ = - r(t)sin(t+ϕ(t)). This change of variable should be regarded as a definition of r(t) and ϕ(t).

Show that r˙ = ε h sin(t+ϕ), rϕ˙=ε h cos(t+ϕ).

Let r(t) = 1t-πt+πr(τ) denote the running average of r over one cycle of the sinusoidal oscillation. Show that drdt = drdt.

Show that drdt = εh[rcos(t+ϕ),-rsin(t+ϕ),t]sin(t+θ).

Show that r(t)= r¯+O() and ϕ(t) = ϕ¯(t)+O(), and therefore dr¯dt = ε(h(r¯ cos(t + ϕ¯)), - r¯ sin(t + ϕ¯), t)sin(t + ϕ¯) + O(ε2)r¯dϕ¯dt= ε(h(r¯ cos(t + ϕ¯)), - r¯ sin(t + ϕ¯), t)cos(t + ϕ¯) + O(ε2).

Concept Introduction:

The expression for the averaging equation for magnitude is x(t,ε) = x0+O(ε).

The expression of initial displacement x0 is x0 = r(T)cos(ϕ(T)).

The expression of the amplitude of any limit cycle for the original system is r=r0+O(ε).

The expression of the frequency of any limit cycle for the original system is ω = 1+εϕ'.

Taylor series expansion of x(t,ε) is x(t,ε)x(t,T)+O(ε). Here, O(ε) are the higher order terms of the Taylor series expansion.

Expert Solution & Answer
Check Mark

Answer to Problem 25E

Solution:

The result r˙ = ε h sin(t+ϕ), rϕ˙=ε h cos(t+ϕ) is proved.

The result drdt = drdt is proved.

The result drdt = εh[rcos(t+ϕ),-rsin(t+ϕ),t]sin(t+θ) is proved.

The results r(t)= r¯+O(), ϕ(t) = ϕ¯(t)+O() and

dr¯dt = ε(h(r¯ cos(t + ϕ¯)), - r¯ sin(t + ϕ¯), t)sin(t + ϕ¯) + O(ε2)r¯dϕ¯dt= ε(h(r¯ cos(t + ϕ¯)), - r¯ sin(t + ϕ¯), t)cos(t + ϕ¯) + O(ε2) are proved.

Explanation of Solution

The expression for the averaging equation for magnitude is:

x(t,ε) = x0+O(ε)

Here, x is the position and x0 is the initial position of the system.

The expression of initial displacement x0 is:

x0 = r(T)cos(ϕ(T))

Here, r(T) is the radius of the polar coordinate system, and ϕ is the angle formed by the radius.

The expression of the amplitude of any limit cycle for the original system is r=r0+O(ε).

The expression of the frequency of any limit cycle for the original system is:

ω = 1+εϕ'

Here, ϕ' is the Taylor series expansion of the function ϕ(T).

Taylor series expansion of x(t,ε) is :

x(t,ε)x(t,T)+O(ε)

Here, O(ε) are the higher order terms of the Taylor series expansion.

(a)

The first derivative of r(t) and ϕ(t) is expressed as follows:

The system equation is:

x¨+x+εh(x,x˙,t) = 0

And,

x(t) = r(t)cos(t+ϕ(t))x˙(t) = -r(t)sin(t+ϕ(t))

Differentiate function x(t) with respect to time,

ddtx(t) = ddtr(t)cos(t+ϕ(t))x˙(t) = r˙cos(t+ϕ)-r(1+ϕ˙)sin(t+ϕ)

Substitute -rsin(t+ϕ) for x˙(t) in the above,

-rsin(t+ϕ)=r˙cos(t+ϕ)-r(1+ϕ˙)sin(t+ϕ)-rsin(t+ϕ) = r˙cos(t+ϕ)-rsin(t+ϕ)-rϕ˙sin(t+ϕ)r˙cos(t+ϕ)rϕ˙sin(t+ϕ) = 0

Further differentiate the function x˙(t) from the above expression,

dx˙(t)dt = d(-r(t)sin(t+ϕ(t)))dtx¨(t) = -r˙sin(t+ϕ(t))-r(1+ϕ˙)cos(t+ϕ(t))

Substitute -r˙sin(t+ϕ(t))-r(1+ϕ˙)cos(t+ϕ(t)) for x¨(t) and r(t)cos(t+ϕ(t)) for x(t) in the above expression of x¨+x+εh(x,x˙,t)

-r˙sin(t+ϕ(t))-r(1+ϕ˙)cos(t+ϕ(t))+r(t)cos(t+ϕ(t))+εh = 0-r˙sin(t+ϕ(t))-rϕ˙cos(t+ϕ(t))+εh = 0r˙sin(t+ϕ(t))+rϕ˙cos(t+ϕ(t)) = εh

From the above calculation of r(t) and ϕ(t), there are two expressions obtained,

r˙cos(t+ϕ)-rϕ˙sin(t+ϕ) = 0r˙sin(t+ϕ(t))+rϕ˙cos(t+ϕ(t)) = εh

Multiply cos(t+ϕ) in equation r˙cos(t+ϕ)-rϕ˙sin(t+ϕ) = 0 and sin(t+ϕ) in equation r˙sin(t+ϕ(t))+rϕ˙cos(t+ϕ(t)) = εh

Therefore, the equation is:

r˙cos2(t+ϕ(t))-rϕ˙sin(t+ϕ(t))cos(t+ϕ(t)) = 0r˙sin2(t+ϕ(t))+rϕ˙cos(t+ϕ(t))sin(t+ϕ(t)) = εhsin(t+ϕ(t)) 

sin2θ+cos2θ=1

Add the above two expression,

r˙cos2(t+ϕ(t)) - rϕ˙sin(t+ϕ(t))cos(t+ϕ(t))+r˙sin2(t+ϕ(t))+rϕ˙cos(t+ϕ(t))sin(t+ϕ(t))=εhsin(t + ϕ(t)) From the trigonometric expression,

sin2θ+cos2θ=1

r˙ = εhsin(t + ϕ(t))

Multiply sin(t+ϕ) in equation r˙cos(t+ϕ)- rϕ˙sin(t+ϕ) = 0 and cos(t+ϕ) in equation r˙sin(t+ϕ(t))+rϕ˙cos(t+ϕ(t))=εh

r˙cos(t+ϕ(t))sin(t+ϕ(t))-rϕ˙sin2(t+ϕ(t))=0r˙sin(t+ϕ(t))cos(t+ϕ(t))+rϕ˙cos2(t+ϕ(t))sin(t+ϕ(t)) = εhcos(t+ϕ(t))

Adding the above expressions,

rϕ˙ = εhcos(t+ϕ(t))

Hence, expression of r˙ and rϕ˙ is rϕ˙=εh cos(t+ϕ(t))r˙=εh sin(t+ϕ(t)).

(b)

The expression for r(t) is given in the question is:

r(t) = 1t-πt+πr(τ)

From Leibniz’s integral rule, considered the function r˙(t) is continuous for τ[t-π, t+π].

Differentiate the above expression,

drdt = ddt(1t-πt+πr(t))drdt = 1(r(t+π)(ddt(t+π))-r(t-π)(ddt(t-π))t-πt+πtr(τ))drdt = 1(r(t+π)(1)-r(t-π)(1)+t-πt+π)drdt = 1(r(t+π)-r(t-π))

drdt = 1t-πt+πdr(τ)drdt = drdt

Hence, expression drdt = drdt is proved.

(c)

drdt = drdtdrdt = r˙(t)

Substitute h(x,x˙,t)sin(t+ϕ) for r˙(t) in above,

r˙(t) = h(x,x˙,t)sin(t+ϕ)

Substitute -r(t)sin(t+ϕ(t)) for x˙(t) and r(t)cos(t+ϕ(t)) for x(t) in the above expression,

r˙(t) = h(r(t)cos(t+ϕ(t)), - rsin(t+ϕ(t)),t)sin(t+ϕ)

Therefore the expression of r˙(t) is

r˙(t) = h(r(t)cos(t+ϕ(t)), - rsin(t+ϕ(t)),t)sin(t+ϕ)

(d)

The magnitude and phase expression for the system equation is calculated as:

Apply Taylor series expansion of r(t) and ϕ(t),

r(t) = r¯ + O(ε)ϕ(t) = ϕ¯+ O(ε)

The above expression is true only because the average value of one oscillation and the rate of change over that cycle,

r = r¯+r˙r = r¯hsin(t+ϕ)r(t) = r¯+O()

ϕϕ¯+ϕ˙ϕϕ¯+r¯hcos(t+ϕ)ϕ(t) = ϕ¯(t)+O()

Therefore, from above expression for r˙(t) and ϕ˙(t),

dr¯dtr˙dr¯dt= ε(h(r¯ cos(t + ϕ¯)), - r¯ sin(t + ϕ¯), t)sin(t + ϕ)dr¯dt= ε(h(r¯ cos(t + ϕ¯)), - r¯ sin(t + ϕ¯), t)sin(t + ϕ) + O(ε)dr¯dt= ε(h(r¯ cos(t + ϕ¯)), - r¯ sin(t + ϕ¯), t)sin(t + ϕ) + O(ε2)

r¯dϕ¯dt = rϕ˙r¯dϕ¯dt= ε(h(r(t) cos(t + ϕ¯)), - r(t) sin(t + ϕ¯), t)cos(t + ϕ¯)r¯dϕ¯dt= ε(h(r¯ cos(t + ϕ¯)), - r¯ sin(t + ϕ¯), t)cos(t + ϕ¯) + O(ε)r¯dϕ¯dt= ε(h(r¯ cos(t + ϕ¯)), - r¯ sin(t + ϕ¯), t)cos(t + ϕ¯) + O(ε2)

Therefore, the expression of dr¯dt and r¯dϕ¯dt is

dr¯dt = ε(h(r¯ cos(t + ϕ¯)), - r¯ sin(t + ϕ¯), t)sin(t + ϕ¯) + O(ε2)r¯dϕ¯dt= ε(h(r¯ cos(t + ϕ¯)), - r¯ sin(t + ϕ¯), t)cos(t + ϕ¯) + O(ε2).

Want to see more full solutions like this?

Subscribe now to access step-by-step solutions to millions of textbook problems written by subject matter experts!
Students have asked these similar questions
Already got wrong chatgpt answer Plz don't use chatgpt answer will upvote
7. Suppose that X is a set, that I is a nonempty set, and that for each i Є I that Yi is a set. Suppose that I is a nonempty set. Prove the following:2 (a) If Y; CX for all i EI, then Uiel Yi C X. ¹See Table 4.8.1 in zyBooks. Recall: Nie X₁ = Vi Є I (x = X₁) and x = Uier X₁ = i Є I (x Є Xi). (b) If XCY; for all i Є I, then X Ciel Yi. (c) U(x)=xnUY. iЄI ΕΙ
8. For each of the following functions, determine whether or not it is (i) injective and/or (ii) surjective. Justify why or why not. (a) fiZZ defined by fi(n) = 2n. (b) f2 RR defined by f2(x) = x² − 4x+7. : (c) f3 Z {0, 1} defined by f3(n) = 0 if n is even and f3(n) = 1 if n is odd. (d) f4 Z N defined by f4(n) = 2n if n > 0 and f4(n) = -2n-1 if n < 0.
Knowledge Booster
Background pattern image
Advanced Math
Learn more about
Need a deep-dive on the concept behind this application? Look no further. Learn more about this topic, advanced-math and related others by exploring similar questions and additional content below.
Similar questions
SEE MORE QUESTIONS
Recommended textbooks for you
Text book image
Algebra & Trigonometry with Analytic Geometry
Algebra
ISBN:9781133382119
Author:Swokowski
Publisher:Cengage
Chain Rule dy:dx = dy:du*du:dx; Author: Robert Cappetta;https://www.youtube.com/watch?v=IUYniALwbHs;License: Standard YouTube License, CC-BY
CHAIN RULE Part 1; Author: Btech Maths Hub;https://www.youtube.com/watch?v=TIAw6AJ_5Po;License: Standard YouTube License, CC-BY